Programa Nacional de Habitação Rural em Alcântara: uma análise a partir das representações dos atendidos através da Associação de Paquatiu - Aragão, Deuzilene Pedra Viegas (2021)
The present work socializes the perceptions of the beneficiaries on the Nacional Rural Habitacional Program (PNHR) in two rural communities of Alcântara. The goal is to present the representations of the beneficiaries about the program deployed by the Association of the Residents and Rural Producers of Paquatiua's Community. In Brazil, the State measure plan in the field of habitacional areas, is aimed to attain the workers necessities, It is recognized by the capacity of organization in this sector and, by the capital juncture, The development of the Captalism System in the country, since the decade of 1930, imposed the State the challenge of deploying politics, including on the habitationa! field. The histórica! process on the struggling for having a home gainned power and challenged the government to invest in politics that respond to their demands. As an answer, the Minha Casa Minha Vida Program (PMCMV) arised as urban and rural fields. The PMCMV brought as a banner the building of units with the same architeture pattem as the last habitacional programs that has being done before. The Quilombola Community of Paquatiua in rural zone of Alcântara, benefited by the PNHR has striking historical and culture features. The implementation of the program brought new elements to the daily life of residents of Alcântara, some of them are urban elements. By measuring the PNHR, the benefited people recognized themselves as subjects from the habitational federal politics. The program were measured by the intreviewers as good or excellent. If s concluded that the PNHR brought to the residents of Alcântara, the possibility to acess the habitational federal politics. Therefore, despite being incipient and contradictory, social policies are necessary, as they contribute to the social reproduction of subjects and to improve their quality of life